Simplifying Reality: The Media’s Portrayal of the Private Prison Debate - Montes, Andrea N. (Crime & delinquency, 2020)
Although the media gives considerable attention to prison privatization, there have been few assessments of how newspapers portray the debate about it and how that portrayal aligns with what is known empirically about private prisons. This study addresses this gap in the literature by undertaking a content analysis of newspaper articles (N = 131) about private prisons and private Immigration and Customs Enforcement facilities, respectively. The results show that few news stories discuss the broad range of factors that scholars highlight as important aspects of the privatization debate. It is also uncommon for news reports, especially those that discuss private immigration facilities, to refer to empirical research or its importance. The implications of this limited portrayal of private facilities are discussed.